(untitled) (Horizontes de Enfermería, 2022)
This research focuses on the development of a Drowsiness detection system applicable to taxi drivers in the city of Tulcán. This arises through the problems found in terms of the large number of traffic accidents that currently occur, being Drowsiness determined as one of the main causes, also because taxi cooperatives do not use any tool to help detect the state of sleepiness of their drivers. These statements were evidenced in the results of quantitative research, where the informants were the taxi drivers of a Tulcán cooperative. With this data, there was the need of developing the drowsiness detection system by applying several electronic tools, especially the infrared obstacle sensor, which is responsible for detecting when the driver closes his eyes for a period of time; a Buzzer alarm device that emits an alarm; moreover, a Bluetooth communication module that establishes the connection between the mobile application and the electronic part. Additionally, a mobile application was developed to manage the electronic part, save its results and users management. To test the operation and effectiveness of the glasses-type prototype, tests were carried out with 20 voluntary users, which can be used in drivers to reduce traffic acidentes because of drowsiness.